(1) 问题背景: 如图 1, 在 $\triangle A B C$ 中, $D$ 为 $A B$ 上一点, 若 $\angle A C D=\angle B$. 求证: $A C^2=A D \cdot A B$;
(2) 尝试应用: 如图 2, 在 $\triangle A B C$ 中, $A B=9, A C=6, D$ 为 $A B$ 上一点, 点 $E$ 为 $C D$ 上一 点, 且 $\frac{D E}{E C}=\frac{1}{2}, \angle A C D=\angle A B E$, 求 $B D$ 的长;
(3) 拓展创新: 如图 3, $\square A B C D$ 中, $E$ 是 $A B$ 上一点, 且 $\frac{A E}{B E}=\frac{1}{2}, E F / / A C$, 连接 $D E$, $D F$, 若 $\angle E D F=\angle B A C, D F=5 \sqrt{6}$, 直接写出 $A B$ 的长.
【答案】 (1) 证明: $\because \angle A C D=\angle B, \angle A=\angle A$
\begin{aligned} & \therefore \triangle A B C \backsim \triangle A C D \\ & \therefore \frac{A B}{A C}=\frac{A C}{A D} \\ & \therefore A C^2=A D \cdot A B \end{aligned}
(2) 解: 过点 $E$ 作 $E F / / A C$ 分别交 $A B$ 于点 $F$.
\begin{aligned} & \therefore \triangle D F E \sim \triangle D A C \\ & \because \frac{D E}{C E}=\frac{1}{2} \\ & \therefore \frac{E F}{C A}=\frac{D F}{D A}=\frac{D E}{D C}=\frac{1}{3} \\ & \therefore E F=\frac{1}{3} A C=2 \end{aligned}
$\therefore$ 设 $D F=x$, 则 $F A=2 x, F B=9-2 x$
\begin{aligned} & \because M N / / A C \\ & \therefore \angle A C D=\angle F E D \\ & \text { 又 } \because \angle A C D=\angle A B E \end{aligned}

\begin{aligned} & \therefore \angle F E D=\angle F B E \\ & \therefore \triangle F E B \subset \triangle F D E \\ & \therefore E F^2=F D \cdot F B \quad \therefore 2^2=x(9-2 x) \cdot \\ & \therefore x_1=4, x_2=\frac{1}{2} \end{aligned}
①当 $x=4$ 时, $B D=9-3 x=-3$ (舍去)
②当 $x=\frac{1}{2}$ 时, $B D=9-3 x=\frac{15}{2}$
$\therefore B D$ 的长为 $\frac{15}{2}$

(3)

\begin{aligned} & \therefore A E=C N, \angle N=\angle B A C \\ & \because \frac{A E}{B E}=\frac{1}{2} \end{aligned}
$\therefore$ 设 $A E=C N=x$, 则 $B E=2 x, C D=3 x, D N=4 x$.

\begin{aligned} & \because \angle E D F=\angle B A C \\ & \therefore \angle E D F=\angle N \\ & \because \triangle D E F \backsim \triangle N E D \cdot 2=2 y=3 \mathrm{y} \cdot 2 \mathrm{y}=6 y^2 \\ & \therefore E D^2=E N \cdot E F=\sqrt{6} y \end{aligned}

\begin{aligned} & \therefore E D=\sqrt{6} y \\ & \therefore \frac{D E}{N E}=\frac{D F}{N D} \text { 即 } \frac{\sqrt{6} y}{3 y}=\frac{5 \sqrt{6}}{4 x} \\ & \therefore x=\frac{15}{4} \\ & \therefore A B=3 x=\frac{45}{4} . \end{aligned}